Impact of neutrophil-to-lymphocyte ratio on effects of targeted therapy for metastatic renal cell carcinoma patients with extrapulmonary metastasis - Teishima, Jun; Ohara, Shinya; Sadahide, Kousuke; Fujii, Shinsuke; Kitano, Hiroyuki; Kobatake, Kohei; Shinmei, Shunsuke; Hieda, Keisuke; Inoue, Shogo; Hayashi, Tetsutaro; Mita, Koji; Matsubara, Akio (Canadian Urological Association Journal, 2017)
Introduction: The aim of our present study was to investigate the impact of the pretreatment neutrophil-to-lymphocyte ratio (NLR) on the antitumour effects of targeted agents in patients with metastatic renal cell carcinoma (mRCC). Methods: The NLRs in 283 cases of molecular targeted therapy for mRCC were measured before starting the prescription of the molecular targeted agent. The significance of pretreatment NLR on the site of metastatic organs and on progression-free survival (PFS) in each case was analyzed. Results: Metastases other than lung, which is defined as “extrapulmonary metastasis,” were observed in 190 cases (67.1%). The median of pretreated NLR was 2.39 (0.49‒68.7). In 97 of the 283 cases, pretreated NLR was 3.0 or higher. These cases were categorized as the high NLR group and the rest as the low NLR group. When the cases with extrapulmonary metastasis were investigated and classified based on their pretreated NLR, 50% PFS in the high NLR and low NLR groups was 6.7 months and 12 months (p=0.0001), respectively. Multivariate analysis revealed that high NLR (>3.0) was an independent predictive factor for PFS in the cases with extrapulmonary metastasis (hazard ratio 2.762; p<0.0001), while there was no significant difference between PFS in the high and low NLR groups in cases with no extrapulmonary metastasis (p=0.3457). Conclusions: Our data indicate that the predictive significance of the NLR in mRCC cases involving targeted therapy depends on the metastatic organs. NLR is an independent predictive factor of PFS in cases of mRCC with extrapulmonary metastasis treated with targeted therapy.